The Utrecht Finite Volume Ice-Sheet Model (UFEMISM) version 2.0 – Part 1: Description and idealised experiments - C. J. Berends; V. Azizi; J. A. Bernales; R. S. W. van de Wal; R. S. W. van de Wal (Geoscientific Model Development)
Projecting the anthropogenic mass loss of the Greenland and Antarctic ice sheets requires models that can accurately describe the physics of flowing ice and its interactions with the atmosphere, the ocean, and the solid Earth. As the uncertainty in many of these processes can only be explored by running large numbers of simulations to sample the phase space of possible physical parameters, the computational efficiency and user-friendliness of such a model are just as relevant to its applicability as is its physical accuracy. Here, we present and verify version 2.0 of the Utrecht Finite Volume Ice-Sheet Model (UFEMISM). UFEMISM is a state-of-the-art finite-volume model that applies an adaptive grid in both space and time. Since the first version published 2 years ago, v2.0 has added more accurate approximations to the Stokes flow, more sliding laws, different schemes for calculating the ice thickness rates of change, a more numerically stable time-stepping scheme, more flexible and powerful mesh generation code, and a more generally applicable discretisation scheme. The parallelisation scheme has changed from a shared-memory architecture to distributed memory, enabling the user to utilise more computational resources. The version control system (git) includes automated unit tests and benchmark experiments to aid with model development, as well as automated installation of the required libraries, improving both user comfort and reproducibility of results. The input/output (I/O) now follows the NetCDF-4 standard, including automated remapping between regular grids and irregular meshes, reducing user workload for pre- and post-processing. These additions and improvements make UFEMISM v2.0 a powerful, flexible ice-sheet model that can be used for long palaeoglaciological applications, as well as large ensemble simulations for future projections of ice-sheet retreat, and that is ready to be used for coupling within Earth system models.